CURVILINEAR CO-ORDINATES AND EXPRESSION OF MOTION EQUATIONS FROM VECTOR FORM TO CYLINDRICAL CO-ORDINATES - MASIBAYI, ANDREW; CYPRIAN, O. S.; OKELO, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we consider at the equations of motion in vector form and convert them to cylindrical coordinates. We also consider the continuity and momentum properties of these equations.